AHP Method of Providing Business Capital Assistance To Information Systems Silumajang Village Bumdes Cooperative During The Covid-19 Pandemic - Ali Akbar Ritonga; Rahmadani Pane (Institute of Computer Science (IOCS), 2021)
The application of the ahp method to the information system in cooperatives managed by the Village-Owned Enterprises (Bumdes) of Silumajang Village, has the goal of making it easier for cooperative members to apply for loans, especially during the corona virus (Covid-19) period. In the application of the Analytical Hierarchy Process (AHP) method as a weighting method for this information system, the weighting used is divided into criteria and sub-criteria, given a value for each criterion and sub-criteria and providing recommendations for feasibility to Bumdes management in determining whether or not members are eligible. customers in getting assistance or loans from village-owned cooperatives (bumdes) with the assessment of each criterion and sub-criteria based on the calculation of the Analytical Hierarchy Process (AHP). With the application of this method, it is hoped that it can provide a solution for management in the midst of limited social interaction in making decisions for members or prospective customers of Cooperatives in borrowing business capital